A new Middle Pleistocene interglacial record from Denmark: Chronostratigraphic correlation, palaeovegetation and fire dynamics. (7th January 2013) - Kuneš, Petr; Kjærsgaard Sørensen, Malene; Buylaert, Jan‐Pieter; Murray, Andrew S.; Houmark‐Nielsen, Michael; Odgaard, Bent Vad
<x xml:space="preserve">Abstract</x> Previously only three terrestrial interglacial periods were known from southern Scandinavia, all of which could be relatively easily correlated within the central European stratigraphical framework. Here, we present a new interglacial–interstadial pollen, plant macrofossil and charcoal record from Trelde Klint, Denmark, and analyse its biostratigraphy, correlation with other European records, vegetation development, fire dynamics and absolute dating. Except for a slight truncation of the early part of the record, the pollen stratigraphy exhibits a full interglacial succession, including temperate trees (Quercus, Ulmus and Tilia) during its mesocratic stage. Macrofossil analysis allowed identification to species level for Quercus robur, Picea abies and two mosses. Conifers (Pinus and Picea) dominate the pollen record of the interglacial sequence, and the occurrence of Larix pollen in the top part of the interglacial record as well as in the interstadial sediments is especially indicative of this interglacial. The overall diversity of tree genera is rather low. These biostratigraphical features suggest that Trelde Klint is unique among Danish records, but it is similar to records from northern Germany. Numerical analyses (REVEALS and DCA) indicate that forests during the temperate stage were dense and that vegetation openness increased only towards the end of the interglacial, accompanied by increased fire occurrence. A short interstadial sequence with a dominance of Pinus and Betula and the presence of Larix is present above the interglacial deposit. We argue that lack of attention to differences in fire regimes may hamper understanding of between‐site correlations of interglacial pollen records. OSL dating, using a novel feldspar technique, yields an average age of 350±20 ka for the sandy sediments above the interglacial layers at Trelde Klint, suggesting that the whole interglacial–interstadial succession belongs to Marine Isotope Stage 11.